A Bis(silylene)-Substituted ortho-Carborane as a Superior Ligand in the Nickel-Catalyzed Amination of Arenes - Zhou, Yu-Peng; Raoufmoghaddam, Saeed; Szilvási, Tibor; Driess, Matthias (Angewandte Chemie International Edition, 2016)
The synthesis and structure of the first 1,2‐bis(NHSi)‐substituted ortho‐carborane [(LSi:)C]2B10H10 (termed SiCCSi) is reported (NHSi=N‐heterocyclic silylene; L=PhC(NtBu)2). Its suitability to serve as a reliable bis(silylene) chelating ligand for transition metals is demonstrated by the formation of [SiCCSi]NiBr2 and [SiCCSi]Ni(CO)2 complexes. The CO stretching vibration modes of the latter indicate that the SiII atoms in the SiCCSi ligand are even stronger σ donors than the PIII atoms in phosphines and CII atoms in N‐heterocyclic carbene (NHC) ligands. Moreover, the strong donor character of the [SiCCSi] ligand enables [SiCCSi]NiBr2 to act as an outstanding precatalyst (0.5 mol % loading) in the catalytic aminations of arenes, surpassing the activity of previously known molecular Ni‐based precatalysts (1–10 mol %). The right bite: A chelating bis‐N‐heterocyclic silylene ligand bridged by an o‐carborane (SiCCSi) and its corresponding Ni complexes (see example) were synthesized, fully characterized, and successfully applied in Ni‐catalyzed Buchwald–Hartwig coupling reactions. [SiCCSi]NiBr2 is the most active precatalyst for this transformation that has been reported to date.